ANALISIS SEKTOR UNGGULAN DAN SEKTOR POTENSIAL DALAM MENINGKATKAN PERTUMBUHAN EKONOMI KABUPATEN 50 KOTA - Diah Wahyuni; Amsah Hendri Doni (CV. ADIBA AISHA AMIRA, 2024)
The background in this research examines leading sectors and the potential of economic areas, which are the main factors for the government to consider in formulating development policies. These two sectors are expected to encourage the development of other business sectors in order to accelerate economic growth. In this study, researchers analyzed superior sectors in the 50 Cities Regency using the Location Quotient (LQ) method, analyzed potential sectors in the 50 Cities Regency using the Shift Share (SS) method, and analyzed economic growth from an Islamic economic perspective. This research uses a descriptive quantitative approach from data on the Gross Regional Domestic Product of 50 Regency Cities with a time series of 2013-2022, this data was collected using observation and literature study methods. The analytical tool in this research uses Location Quotient (LQ) and Shift Share (SS) analysis. The results of the research show that three economic sectors that are well developed as the main sectors in the 50 City Districts in 2013-2022 are agriculture, forestry, fisheries with a coefficient of 1.50; mining, excavation with a coefficient of 1.89; and health services have a coefficient of 1.03. And there are six economic sectors that are well developed to encourage economic growth, namely sectors whose presence is above the 45º diagonal in the 50 City Districts for the 2013-2022 period, namely agriculture, forestry and fisheries; mining and excavation; processing/manufacturing industry; transportation, warehousing; financial services, insurance; and the corporate ADM sector, these six sectors are very useful because of their rapid growth compared to other sectors. In Islamic economics, economic growth can produce sufficient needs for society and is free from financial obstacles, except for obstacles to Allah SWT in meeting needs so as to provide prosperity in this world and the hereafter